Translation Techniques Used to Transfer Legal Culture to the Criminal Offences (Sentencing and Execution) Act, 2017 - Bhattarai, Achyutananda (Medha: A Multidisciplinary Journal, 2026)
This research examines the translation techniques used to transfer legal culture to the Criminal Offences (Sentencing and Execution) Act 2017 of Nepal, focusing on the conveyance of sentencing and execution principles to the criminal justice system. The study claims that the source language (SL) legal culture can be transferred to the target language (TL) using various translation techniques, which are determined by the nature of the text, the purpose of translation, and the readers' knowledge of comparative laws and legal systems, and explores the translation techniques applied to transfer the English penal culture to the mentioned law. It reviews the translation techniques used in words, sentences, grammar, and text at both the linguistic and extra-linguistic cultural levels using the translation technique of Vinay and Darbelnet. The significance of the study is for translation students and novice translators who learn how translation techniques are used to transfer culture from one language and legal system to another. This search concludes that competence in translation techniques enables translators to transfer the SL culture into the TL.